The impact of At1r inhibition via losartan on the anti-leukaemic effects of doxorubicin in acute myeloid leukaemia. (May 2019) - Ghasemi, Mehdi; Okay, Mufide; Turk, Seyhan; Naeemaee, Ronak; Guver, Ebru; Malkan, Umit Y; Aksu, Salih; Sayinalp, Nilgun; Haznedaroglu, Ibrahim C
Introduction: Bone marrow renin–angiotensin system(RAS) modulates acute myeloid leukaemia(AML).The aim of this study is to clarify the relationships between RAS and AML, and to show the effect of losartan and doxorubicin treatment in AML cell lines. Methods: AML cell lines including CESS, HL-60, MO-1, P31/FUJ, GDM-1 and KASUMI-3 were used as models in this study. Results: After treating the six AML cell lines with a combination of losartan and doxorubicin, they were divided into two groups based on their behaviour: one became more sensitive to drug treatment (Group A) and the other had no change observed in behaviour after drug treatment (Group B). In silico analyses showed that Group A is involved in cellular apoptosis, while Group B is involved in tumour angiogenesis further supporting the in vitro results. Conclusion: The combined treatment of the AML cell lines with losartan and doxorubicin resulted in an increase in sensitivity of some of the cell lines. Those leukaemic cells are modulated via the induction of apoptosis, whereas the other cells resistant to the drug treatment are closely related to tumour angiogenesis indicating that RAS-AT1R seems to be differently expressed in different leukaemic blast cells and tumour microenvironments. Pharmaco-biological actions of RAS inhibitors may be different in distinct leukaemic cells based on the pathological behaviour of AML genomic subtypes.